An Islandwide Struggle for Freedom : Revolution, Emancipation, and Reenslavement in Hispaniola, 1789-1809 - Nessler, Graham T. (Book collections on Project MUSE., 2016)
Reinterpreting the Haitian Revolution as both an islandwide and a circum-Caribbean phenomenon, Graham Nessler examines the intertwined histories of Saint-Domingue, the French colony that became Haiti, and Santo Domingo, the Spanish colony that became the Dominican Republic. Nessler argues that the territories' borders and governance were often unclear and mutually influential.